Group photograph with James C. Goble - Unknown:::Creator::::::::::::
Photograph shows Miss Melody Meuckers taking tickets from Mr. James C. Goble while his wife watches. Both women have gloves and Mrs. Goble is wearing a fur stole and a corsage. Mr. Goble is dressed in a suit and tie.